Community Factor Analysis of Demand Dental Health Services in the Era New Normal - Dayinta Annisa Syaiful; Indriati Paskarini; Tri Martiana; Aprilia Dwi Purwanti; Dandi Widhi Ramadhan; Eka Safitri Silehu (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Dental health problems cannot be ignored because they will impact health. Moreover, many people often experience toothache, but only a small percentage access dental and oral health services in the New Normal era. This is based on the results of preliminary research on 112 respondents. As many as 69.60% of respondents had dental and oral health problems, but only 31.30% accessed dental and oral health services during the adaptation period to new habits. This encouraged researchers to research Community Factor Analysis of Dental Health Service Reports in the new normal era. This research aims to determine the need and demand for dental and oral health services located in Surabaya in the era of Adaptation to New Habits. This research method uses a quantitative descriptive research design. The research was conducted in Surabaya in January 2019. The sampling technique was non-random sampling. The population in the study was 3.095.026 residents of Surabaya City, so the sample for this study was 394 people. The data collection technique was carried out by filling out a questionnaire. The data obtained was then analyzed using univariate analysis using descriptive data tabulation. The research results show that the older the age, the higher the demand for dental health services (42.9%). In addition, women have higher demands than men (30.0%). Finally, negative perceptions of health greatly influence demands for dental care (63.6%). Based on the research results, respondents' use of dental and oral health services is still low, and their needs and demands still need to be met. It is recommended that oral health be promoted through social media and that this research be used to engage oral health services. Keywords: Need Dental, New Normal, Oral Health Services